Recognition and Enforcement of International Arbitral Awards in Albania. Current hallenges to the Albanian Domestic Law - Spahiu, Artan (European Journal of Multidisciplinary Studies, 2017)
The Convention on the Recognition and Enforcement of Foreign Arbitral Awards (the New York Convention) is described as the most successful treaty in private international law. For more than half a century this document has contributed to the protection of incomparable values of free trade. In this way it served well also to the interests of human society, providing a valuable contribution to the world economic development. Legal instruments of recognition and enforcement of foreign arbitral awards in the Republic of Albania do not justify the rightful place of arbitration mechanism in resolving international commercial disputes. The domestic normative framework that governs the enforcement of such awards is not fully sufficient. Albania has ratified the New York Convention more than 40 years after its entry into force, but that's not enough. In fact, the enforcement of arbitral awards which resolve international commercial disputes is facing with the lack of a modern legal framework and an unconsolidated jurisprudence. Since last 15 years, the New York Convention is part of Albanian legal order, but its implementation is not appropriate. Mostly this is due to the lack of approaching process of the Albanian legislation to the international standards in this field. Adoption and implementation of legal instruments in accordance with the international legal framework, for the recognition and enforcement of foreign arbitral awards, will be a good service to the integration process of the Albanian economy.
Keywords: arbitration, convention, enforcement, award, disputes, international.